Multimodal Literacy in School Science Transdisciplinary Perspectives on Theory, Research and Pedagogy - Unsworth, Len (Taylor & Francis, 2022)
This book establishes a new theoretical and practical framework for multimodal disciplinary literacy (MDL) fused with the subject-specific science pedagogies of senior high school biology, chemistry and physics. It builds a compatible alignment of multiple representation and representation construction approaches to science pedagogy with the social semiotic, systemic functional linguistic-based approaches to explicit teaching of disciplinary literacy. The early part of the book explicates the transdisciplinary negotiated theoretical underpinning of the MDL framework, followed by the research-informed repertoire of learning experiences that are then articulated into a comprehensive framework of options for the planning of classroom work. Practical adoption and adaptation of the framework in biology, chemistry and physics classrooms are detailed in separate chapters. The latter chapters indicate the impact of the collaborative research on teachers' professional learning and students' multimodal disciplinary literacy engagement, concluding with proposals for accommodating emerging developments in MDL in an ever-changing digital communication world. The MDL framework is designed to enable teachers to develop all students' disciplinary literacy competencies. This book will be of interest to researchers, teacher educators and postgraduate students in the field of science education. It will also have appeal to those in literacy education and social semiotics.